Общенаучные средства и формы познания в библиографоведении - Янонис, Освальдас (Knygotyra, 1983)
In the present article the methodological meaning of universal ways and means of cognition to the analysis of bibliographical objects has been dealt with. It has been concluded that the ways and means are instrumental to optimum knowledge of bibliographical objects. The methodological meaning of the universal concept “system” in the definition of the term “system of bibliographical means” has been analysed in detail. The system of bibliographical means has been treated as a functioning component of a more complex system.